Competing factors on the frequency separation between the OH stretching modes in water - Zhang, Chao; Guidoni, Leonardo; Kühne, Thomas D. (Journal of Molecular Liquids, 2015)
Recent simulations demonstrated that the inhomogeneous broadening as observed in the vibrational spectra of liquid water at ambient conditions can be viewed as a large vibrational splitting of symmetric and asymmetric OH stretching modes, due to the asymmetry of the local hydrogen-bonding network [J. Phys. Chem. Lett., 2013, 4(19), pp 3245-3250]. In this work, we show that the finite temperature and the liquid phase do not only modulate the local hydrogen-bonding asymmetry of water molecules, but also the intramolecular coupling strength. These two factors compete together in the determination of the overall magnitude of the frequency separation between the two OH stretching modes in water at ambient conditions.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Ab initio molecular dynamics; Biological water; Inhomogeneous broadening; Interfacial water; Vibrational spectroscopy